HUMAN RESOURCES MANAGEMENT IN ISLAMIC EDUCATION: EXPERTISE, TRAINING AND PERFORMANCE - Jamrizal Jamrizal (Dinasti International Journal of Education Management And Social Science, 2022)
The Literature Review article on Human Resource Management in Islamic Education: Expertise, Training and Performance is a scientific article that aims to build a research hypothesis on the relationship between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Expertise related to Human Resource Management in Islamic Education; 2) Training related to Human Resource Management in Islamic Education; and 3) Performance related to Human Resource Management in Islamic Education. Apart from the 3 exogenous variables that are related to the endogenous variables of Human Resource Management in Islamic Education, there are other related factors including the variables of Leadership, Rewards, Recruiting and Research.